Biblical Words and Phrases in the Representation of Slavic Folk Speech - Variuchina, Jelena I. (Respectus Philologicus, 2006)
More than a thousand years ago, the Slavs adopted Christianity. The new Christian ideology entered the people’s minds. But the ancient pagan ideas were still alive. Not only does Slavic folklore keep them, but the word by itself reveals the traces of these archaic ideas. Even the Bible words and phrases often get a new meaning in popular speech and begin to express Christian views and the "shadows of ancient beliefs". The article analyses the character of functioning and semantics of biblical words and phrases in folk speech.